2014
DOI: 10.1044/2014_ajslp-13-0050
|View full text |Cite
|
Sign up to set email alerts
|

Can Human Mannequin-Based Simulation Provide a Feasible and Clinically Acceptable Method for Training Tracheostomy Management Skills for Speech-Language Pathologists?

Abstract: These findings validate the use of simulation as a clinical training medium and support its future use in tracheostomy competency-training pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 39 publications
1
17
0
3
Order By: Relevance
“…Equally, it is possible that working through only two (quite different) immersive scenarios was not sufficient to achieve change (particularly for students with limited clinical experience), and perhaps working through multiple scenarios may have had a different outcome. Ward et al (2014) found significant, large increases in the clinical decision-making skills of practicing clinicians who were provided the opportunity to work through nine HPS scenarios in one day relating to tracheostomy management. The potential benefit of completing multiple scenarios to improve clinical decision-making for less experienced student clinicians needs further examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally, it is possible that working through only two (quite different) immersive scenarios was not sufficient to achieve change (particularly for students with limited clinical experience), and perhaps working through multiple scenarios may have had a different outcome. Ward et al (2014) found significant, large increases in the clinical decision-making skills of practicing clinicians who were provided the opportunity to work through nine HPS scenarios in one day relating to tracheostomy management. The potential benefit of completing multiple scenarios to improve clinical decision-making for less experienced student clinicians needs further examination.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical environment was simulated, significant effort was made to enhance the realism of the scenarios in order to help facilitate learning (Blackstock & Jull, 2007). Previous research using HPS to train tracheostomy management skills with practicing SLPs revealed that participants found the HPS scenarios and working with mannequins to be very realistic (Ward et al, 2014). Similarly, the current group of students commented on the realistic clinical nature of the activities, the opportunity to practice clinical and communication skills, and the opportunity to get 'hands on', as benefits of the HPS program.…”
Section: Discussionmentioning
confidence: 99%
“…For example, standardised patients have been used to teach communication and interpersonal skills (Zraick, Allen, & Johnson, 2003), interviewing skills, client education, responses to confrontation, and administration of therapy techniques (Syder, 1996). SLEs have also been used to train advanced specialised clinical skills, such as the management of tracheostomised patients (Ward et al, 2014). There is, however, limited literature in speech-language pathology education on the applications of virtual-based SLEs for clinical training.…”
Section: Simulated Learning Environmentsmentioning
confidence: 99%
“…A avaliação do desempenho prático nos referidos estudos com uso de simuladores de pacientes na Fonoaudiologia tem sido realizada principalmente a partir da aplicação de questionários de percepção do estudante ou profissional sobre sua aprendizagem durante a interação com os simuladores de pacientes 60,62 . Outras formas de avaliação contemplam a observação das habilidades e técnicas demonstradas pelo estudante ou profissional perante situações em que precisa solucionar problemas, a partir de sua interação com o simulador, dentro de um contexto clínico ou hospitalar 57,60 .…”
Section: Descritoresunclassified
“…Outras formas de avaliação contemplam a observação das habilidades e técnicas demonstradas pelo estudante ou profissional perante situações em que precisa solucionar problemas, a partir de sua interação com o simulador, dentro de um contexto clínico ou hospitalar 57,60 . A aplicação dos métodos de aprendizagem foi realizada durante sete semanas, tempo de duração total da disciplina formal.…”
Section: Descritoresunclassified